NANOTECNOLOGIA EM FÁRMACOS: PROSPECÇÃO TECNOLÓGICA NO ÂMBITO NACIONAL E INTERNACIONAL - FIALKOSKI, DIEGO (2020)
Nanotechnology is configured as a technological application that studies matter at the nanoscale, atomic and molecular scale, objects with physical dimensions between 1 and 100 nm. This technology is used in the modernization of industrial and technological sectors. That said, the present research aims to map studies (of technological innovation) specifically on the use of nanotechnology in the field of drugs, in order to verify the growth of patent deposits in Brazil and in the world. Thus, the prospective study developed analyzed the advancement of research in nanotechnology precisely in the publication of scientific articles in the period from 1980 to 2018 and in the filing of patent applications in the period from 2010 to 2018. The databases searched were the Coordination Periodical for the Improvement of Higher Education Personnel, for articles, and the Patentscope of the World Intellectual Property Organization, for filing patents. Given the interdisciplinary application in physics, chemistry, biology, engineering, computing and in the field of medicine, nanotechnology allows its application in several fields of research. It was concluded that the numbers of articles and patents in Brazil are significant, as they exceed the values in relation to countries such as Portugal and Mexico.